2020
DOI: 10.5125/jkaoms.2020.46.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for postoperative nausea and vomiting in orthognathic surgery: a 10-year retrospective study

Abstract: Objectives: Postoperative nausea and vomiting (PONV) is considered as one of the most incessant and anguishing factors for patients who have surgery under general anesthesia. The occurrence of PONV after orthognathic surgery can lead to dehydration, infection, bleeding at the surgical site, and patient discomfort, all of which leave a patient with a negative impression of anesthesia and surgery. The purpose of this study is to assess the incidence of PONV after orthognathic surgery and to correlate it with fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 54 publications
0
25
3
Order By: Relevance
“…This was in accordance with the results of a previous meta-analysis [ 36 ], showing that liberal intraoperative fluid regimens had lower odds of developing PONV as compared with restrictive fluid regimens. However, a recent study [ 51 ] showed that a higher occurrence of PONV was found in patients undergoing orthognathic surgery with more intraoperative fluid supply than those with less (≥25 mL/kg vs. <25 mL/kg). Although this study was a 10-year retrospective study, only 101 patients were included, and all factors were considered individually as in our basic statistics ( Table 1 ) which did not detect interactions of different potential risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with the results of a previous meta-analysis [ 36 ], showing that liberal intraoperative fluid regimens had lower odds of developing PONV as compared with restrictive fluid regimens. However, a recent study [ 51 ] showed that a higher occurrence of PONV was found in patients undergoing orthognathic surgery with more intraoperative fluid supply than those with less (≥25 mL/kg vs. <25 mL/kg). Although this study was a 10-year retrospective study, only 101 patients were included, and all factors were considered individually as in our basic statistics ( Table 1 ) which did not detect interactions of different potential risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In accord with its elimination half-life, the antiemetic effect of penehyclidine is diminished or disappeared after 24 h [ 14 , 15 ]. However, PONV following orthognathic surgery may persist for up to 96 h [ 16 ]. We, therefore, tested the hypothesis that a bolus plus infusion administration of penehyclidine could be more effective in reducing PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that prophylactic penehyclidine administered before surgery helped to prevent PONV [ 14 , 15 ]. Since the mean elimination half-life of a single-dose penehyclidine is about 10.35 h, whereas high frequent PONV may persist for up to 96 h after orthognathic surgery [ 16 ], we hypothesize that a low-dose bolus plus continuous infusion of penehyclidine may be more effective for PONV prevention. The purpose of this study is to investigate the efficacy and safety of single-dose plus continuously administrated penehyclidine in preventing PONV in patients undergoing bimaxillary surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of intraoperative fluid therapy on PONV remains inconclusive. A large number of studies in a 10-year retrospective study in orthognathic surgery in Asia revealed that the more the intraoperative intravenous fluids administered, the higher the occurrence of PONV [ 9 ]. A systematic review and meta-analysis of 41 studies from the Cochrane Database showed that perioperative intravenous crystalloid supplementation could reduce PONV [ 10 ].…”
Section: Discussionmentioning
confidence: 99%